Atomic scale observation of threading dislocations in α-Ga2O3 - Ross Mullen; Joseph W. Roberts; Paul R. Chalker; Rachel A. Oliver; Ben Hourahine; Fabien C. P. Massabuau (AIP Advances)
This study presents a statistically significant investigation of threading dislocations in α-Ga2O3 using high-resolution transmission electron microscopy. All the dislocations, observed end on, exhibit a projected Burgers vector be=13⟨11̄00⟩, with data revealing that the dislocations fall into three categories: perfect mixed (b=13⟨11̄01⟩) dislocations and edge (b=⟨11̄00⟩ and b=13⟨112̄0⟩) dislocations, which dissociate into combinations of b=13⟨11̄00⟩ partials. High-resolution analysis of the core region of the dislocations identifies that all the dislocations exhibit a similar 5-atom core, when looking at the cation sites. This is the first investigation of its kind in this material system, which will inform future work to, for example, understand the electronic properties of dislocations in α-Ga2O3 and other epitaxial corundum-structured materials.